From Perviousness to Plaque Imaging in Acute Basilar Occlusions: The Impact of Underlying Stenosis and How to Detect It. Issue 3 (March 2020) - Berndt, Maria T.; Pree, David; Kaesmacher, Johannes; Maegerlein, Christian; Friedrich, Benjamin; Zimmer, Claus; Wunderlich, Silke; Mück, Fabian G.; Wirth, Stefan; Boeckh-Behrens, Tobias
Abstract : Background and Purpose—: Recent studies show that mechanical thrombectomy of acute basilar artery occlusions (BAO) results in high rates of successful recanalization and good outcomes, but predictors are not completely established yet. Varying occlusion types may benefit differently, and especially, an underlying basilar stenosis (BS) seems to have an impact. Aim of this study was to investigate angiographic and clinical differences in BAO subtypes and to test the potential of perviousness measures for a preinterventional identification of clinically relevant different occlusion types. Methods—: All consecutive patients with acute BAO, endovascular treated at a single comprehensive stroke center, were included. Different occlusion patterns, especially underlying BS, were identified and analyzed in respect of angiographic and clinical (National Institutes of Health Stroke Scale/modified Rankin Scale) outcome parameters (N=115). Thrombus perviousness measures (change in thrombus attenuation Δt and corrected void fraction ε) were assessed in admission computed tomography imaging and correlated to different etiological subgroups. Results—: Despite comparable rates of successful recanalization (87% for BAO with BS versus 95% without BS), the BS group showed worse clinical outcome with higher National Institutes of Health Stroke Scale/modified Rankin Scale values ( P =0.002/0.003). The group of BS turned out to have lower thrombus density values in unenhanced scans (mean, 42.0 Hounsfield units) and higher perviousness measures Δt (mean, 34.6 Hounsfield units) and ε (mean, 0.23) than thrombi without an underlying BS (mean, 53.6 Hounsfield units/13.1 Hounsfield units/0.08, P =0.01/ 0.004/ 0.001). Conclusions—: In agreement with previous studies, outcome of mechanical thrombectomy of BAO seems to depend on pathogenesis with less clinical benefit for underlying BS, raising the question of early identification of this subgroup. Perviousness showed a high potential to differentiate acute BAO with and without BS, possibly usable as an admission imaging marker for BS. Abstract : Supplemental Digital Content is available in the text.